オットセイ仔獣の発生音の個体差について - Takemura, Akira; Yoshida, Kazumoto; Baba, Norihisa (長崎大学水産学部, 1983)
The calls of six northern fur seal pups, Callorhinus ursinus, transported from Robben Island to Mito Sea Paradise were analized. The calls of northern fur seal pups consist of a short one of a few-tenths of a second and a shriek type of 1-2 seconds or longer. They have frequency components which range from a few-tens Hertz to eight kilo-Hertz. Each call consists of a clear main peak frequency and a sub-main peak frequency. The call of each pup has a characteristic structure which hardly changes according to the physiological condition. It is considered that a mother seal distinguishes the call of the pup and uses it as the first clue to find her pup. ロベン島で捕獲され,三津シーパラダイスに搬入されたオットセイ仔獣6頭の発生音を解析した.オットセイ仔獣の発生音は1秒の数分の1の短いものと,1～2秒,時には数秒持続する大きなワメキ音で,数十Hzから8kHz以上にも達する周波数成分より成る.各発生音は顕著な主極大周波数と副極大周波数より成る.各仔獣の発生音は各々特徴的な構造を有し,発音時の生理的状態によって大きく変わることはない.母獣はこれらの発生音を識別して,自己の仔獣を発見する最初の手掛りとしていると考えられる. 長崎大学水産学部研究報告, v.54, pp.29-34; 1983 departmental bulletin paper